(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Curriculum Ideological and Political Education (CIPE) is a comprehensive educational concept. Integrating ideological and political education into subject teaching can effectively promote students’ political consciousness, and enhance their national self-esteem, pride, and national identity. This study adopts empirical research, focusing on eighth-grade students and English teachers at a middle school in Lufeng City. Using survey questionnaire and teacher interviews, it explores the current status of integrating Curriculum Ideological and Political Education into teaching of English reading in junior high school. The main research questions include: (1) What is the overall understanding of junior high school students and teachers on integrating Curriculum Ideological and Political Education into English reading teaching? (2) What is the impact of integrating Curriculum Ideological and Political Education into English reading teaching on the emotional attitude and values of junior high school students? (3) What specific approaches do English teachers employ to integrate Curriculum Ideological and Political Education into junior high school English reading teaching? The survey results show that students generally support the integration of CIPE into reading teaching, and teachers also recognize its advantages. However, teachers face challenges in putting it into practice. This study identifies the problems of integrating CIPE into teaching reading through experimental data analysis and proposes corresponding solutions, aiming to innovate the research on junior high school English reading.